AFM-based pick-and-place handling of individual nanoparticles inside an SEM for the fabrication of plasmonic nano-patterns - Mick, Uwe; Banzer, Peter; Christiansen, Silke; Leuchs, Gerd (Optics InfoBase Conference Papers, 2014)
Integrating AFM technology into an SEM enables the interactive assembling of individual nanoparticles by in-situ pick-and-place handling. We present a hardware setup and introduce examples for the nanofabrication of plasmonic patterns. © 2014 OSA.
CRIS-Team Scopus Importer:2023-03-07